Mutation analysis of the WNT4 gene in Han Chinese women with premature ovarian failure - Zhou Sirui; Yang Lu; Wang Jing; Wang Binbin; Suo Peisu; Chen Beili; Zhu Ying; Ma Xu; Cao Yunxia (BMC, 2011)
Abstract Background The WNT4 gene plays an important role in female sex determination and differentiation. It also contributes to maintaining of the ovaries and the survival of follicles. Methods We sequenced the coding region and splice sites of WNT4 in 145 Han Chinese women with premature ovarian failure (POF) and 200 healthy controls. Results Only one novel variation, in Exon 2 (195C > T), was detected among the women with POF. However, this synonymous variation did not result in a change in amino acid sequence (65 Asp > Asp). No further variants were found in any of the samples. Conclusion Although we cannot provide any evidence that it is a possible disease-causing gene, this study is the first attempt to investigate the possible role of WNT4 in Han Chinese women with POF.